Development and Training of Islamic Religious Education Supervisors in the Implementation of the Independent Curriculum - Nursikah Intan; Mesiono Mesiono; Khadijah Khadijah (Newinera Publisher, 2026)
This study aims to analyze the mechanism of competency development and the supervision patterns of Islamic Education supervisors (PAI) in supporting the implementation of the Merdeka Curriculum in Simalungun Regency. Using a qualitative approach with a multi-site study design, data were collected through in-depth interviews, observations, and documentation involving PAI supervisors, teachers, principals, and related parties from three non-driving public elementary schools. The results of the study indicate that the role of PAI supervisors has contributed to improving teachers' understanding of learning tools, assessment, and the strengthening of religious character, although the communication pattern applied is still predominantly top-down and not yet fully participatory. The main challenges encountered include the limited technological competence of teachers, infrequent supervision due to the wide coverage of mentees, and uneven support in terms of facilities and institutional resources. This study emphasizes the need to develop a coaching and mentoring-based guidance model and to optimize inter-institutional collaboration through the use of information technology as an effort to strengthen supervisors' capacity as agents of change. These findings have implications for formulating a more adaptive, sustainable, and contextual supervisory guidance strategy for PAI supervisors in supporting the implementation of the Merdeka Curriculum in non-pioneer regions.